Sanitizing evaluation of the extracts of mastruz (Chenopodium ambrosioides) and garlic (Allium sativum) on nematodes of the genus Strongyloides sp. and Ancylostoma sp. in vegetables (Revista Brasileira de Plantas Medicinais, 2020)
Poor sanitation of contaminated vegetables has led to parasitic diseases and has become a public health problem. Vegetables benefit the organisms, but they can also contribute to the spread of parasitic diseases. Thus, sanitation becomes essential for the precaution of these diseases, and this is a critical stage, since the products responsible for disinfecting these foods can harm individuals. Therefore, this article aims to evaluate the extracts of mastruz (Chenopodium ambrosioides) and garlic (Allium sativum) as possible sanitizers. The collection and preparation of aqueous extracts of mastruz and garlic were carried out at a concentration of 11.11%, using the method of Rugai, Mattos and Briola in some specimens of vegetables, after an action of these extracts on the nematodes from these individuals. The pieces presented that Strongyloides sp. and Ancylostoma sp., had their movements reduced, without causing their total immobilization. Therefore, the exact results of the data that the innate extracts did not show actions or nematostatics, nor reduced to a minute movement.